Patient Factors, Donor Age, and Graft Storage Duration Affect Osteochondral Allograft Outcomes in Knees with or without Comorbidities - Nuelle, Clayton W.; Nuelle, Julia A.V.; Cook, James L.; Stannard, James P. (The Journal of Knee Surgery, 2017)
Limited data exists defining preoperative variables that affect outcomes after osteochondral allograft transplantation (OAT) in the knee. In this retrospective study, we examined 75 patients who underwent OAT for large (≥2 cm2) grade IV cartilage defects in the femoral condyle. Patient variables evaluated included the following: smoking, workers compensation, body mass index (BMI), pre-injury activity level, number, and the type of co-morbidities in the operated knee, lesion location and number of grafts placed. OCA donor age and graft storage duration from procurement were also evaluated. Preoperative and postoperative visual analogue scale (VAS) pain scores were the primary outcome measure. Overall, 53 patients (71%) had successful outcomes, with 81% of patients without co-morbidities having successful outcomes. Active patients were significantly (p = 0.023) more likely to have a successful outcome than low activity patients. Patients with BMI <35 were 4 times more likely to have a successful outcome (p = 0.01). There were no significant differences based on donor age. Patients with transplanted grafts stored >28 days were significantly (p = 0.048) and 2.6 times more likely to have an unsuccessful outcome. This study provides new evidence for preoperative patient factors and graft variables that may influence the overall outcome after osteochondral transplantation in the knee.
Keywords: osteochondral allograft; osteochondral transplant; cartilage defects; osteochondral storage